A Scoping Review of Life-Course Psychosocial Stress and Kidney Function - Jesus Alejandro Estevez-Garcia; Marcela Tamayo-Ortiz; Alison P. Sanders (MDPI AG, 2021)
Increased exposure to maternal psychosocial stress during gestation and adverse neonatal environments has been linked to alterations in developmental programming and health consequences in offspring. A programmed low nephron endowment, among other altered pathways of susceptibility, likely increases the vulnerability to develop chronic kidney disease in later life. Our aim in this scoping review was to identify gaps in the literature by focusing on understanding the association between life-course exposure to psychosocial stress, and the risk of reduced kidney function. A systematic search in four databases (PubMed, ProQuest, Wed of Science, and Scopus) was performed, yielding 609 articles. Following abstract and full-text review, we identified 19 articles meeting our inclusion criteria, reporting associations between different psychosocial stressors and an increase in the prevalence of kidney disease or decline in kidney function, mainly in adulthood. There are a lack of studies that specifically evaluated the association between gestational exposure to psychosocial stress and measures of kidney function or disease in early life, despite the overall evidence consistent with the independent effects of prenatal stress on other perinatal and postnatal outcomes. Further research will establish epidemiological studies with clear and more comparable psychosocial stressors to solve this critical research gap.